Institutional approaches to the planning of sustainable use and protection of agricultural lands on the territory of individual land uses - Dorosh, O.; Dorosh, A.; Saliuta, V.; Melnyk, D. (Land Management, Cadastre and Land Monitoring, 2023)
The concepts of institutions and institutional approaches are studied. On the basis of institutional approaches to the planning of sustainable use and protection of agricultural lands of individual land uses, a system of institutes was formed, which include: the Institute of Land Management, the Institute of Land Monitoring, the Institute of the State Land Cadastre, the Institute of Local Self-Government, and the Institute of Local Traditions. The importance and effectiveness of these institutions, namely as systems and their relevance, are substantiated. The tools of these institutes, which allow for planning the sustainable use and protection of agricultural lands of individual land uses, as well as their implementation, have been analysed.The institute of land management and its tools, such as land management schemes and technical and economic justifications for the use and protection of lands of administrative territorial units, territories of territorial communities, and complex plans for the spatial development of the territory of the territorial community, are analysed in detail. The need to introduce a tool of land management regulations to expand the possibilities of the institute of land management in planning the use of territories located outside of settlements is justified. The importance of the institution of land monitoring is substantiated and the urgency of creating and implementing an automated land monitoring system is emphasized. The current state of the Institute of the State Land Cadastre was investigated and the expediency of expanding the list of objects of the State Land Cadastre by adding "agricultural land use" was substantiated. It was found that the significance of the institution of local self-government in the context of planning the sustainable use and protection of agricultural lands of individual land uses increases due to the expansion of the powers of local authorities in the process of decentralization of power. The need to take into account local agricultural traditions when planning the sustainable use and protection of agricultural lands of individual land uses has been confirmed.
Keywords: institutions; institutional approaches; agricultural land; land use; sustainable use and protection of agricultural land; land management; State Land Cadastre; local self-government.